2019
DOI: 10.1039/c9an00243j
|View full text |Cite
|
Sign up to set email alerts
|

A near-infrared fluorescent probe for evaluating endogenous hydrogen peroxide during ischemia/reperfusion injury

Abstract: A fluorescent probe, Cy-ArB, is developed for real-time monitoring of H2O2 fluctuations in cells and in vivo during ischemia/reperfusion processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Reactive oxygen species (ROS), inducing extensive degradation of the extracellular matrix of cartilage and extracellular toxicity to intra-articular tissues via DNA damage and modifying the lipid, , plays an essential role in the onset and progression of OA. , Thus, clearing the high levels of intracellular ROS may further reinforce therapeutic efficacy in OA . In recent years, ROS-responsive nanoparticles have been extensively studied and applied with the swift development of biomedical materials, and plenty of nanocarriers have presented the adequate advantage of ROS responsiveness and ROS consumption. For instance, Tang et al used a combination of living anionic ring-opening polymerization of poly­(propylene sulfide) and atom transfer of the radical to prepare polymeric micelles, which efficiently responded to the intracellular ROS and simultaneously released the drugs. In the treatment of OA, ROS-responsive polymeric micelles can both encapsulate hydrophobic drugs (i.e., KGN and Dex) in the core to achieve an ROS-responsive release behavior and decrease the levels of ROS.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS), inducing extensive degradation of the extracellular matrix of cartilage and extracellular toxicity to intra-articular tissues via DNA damage and modifying the lipid, , plays an essential role in the onset and progression of OA. , Thus, clearing the high levels of intracellular ROS may further reinforce therapeutic efficacy in OA . In recent years, ROS-responsive nanoparticles have been extensively studied and applied with the swift development of biomedical materials, and plenty of nanocarriers have presented the adequate advantage of ROS responsiveness and ROS consumption. For instance, Tang et al used a combination of living anionic ring-opening polymerization of poly­(propylene sulfide) and atom transfer of the radical to prepare polymeric micelles, which efficiently responded to the intracellular ROS and simultaneously released the drugs. In the treatment of OA, ROS-responsive polymeric micelles can both encapsulate hydrophobic drugs (i.e., KGN and Dex) in the core to achieve an ROS-responsive release behavior and decrease the levels of ROS.…”
Section: Introductionmentioning
confidence: 99%
“…Real-time detection of changes in O 2 *À levels may be beneficial for medical diagnosis. Finally, this study showed that cyanine 73 can be used to pre-evaluate clinical surgeries.Inspired by the changes in endogenous superoxide anions during I/R injuries, [96] Xu et al [97] synthesized heptamethine cyanine dye 75 to evaluate the relationship between H 2 O 2 , a downstream product of the superoxide, and organ damage during liver I/R. This cyanine was designed by uniting two different parts: a heptamethine cyanine dye (NIR fluorophore) and a boronate ester group (response unit) (Figure 16a).…”
Section: Bioimagingmentioning
confidence: 99%
“…After this seminal study, aryl boronic acid-capped fluorophores remain a prevalent strategy in the selective detection of H 2 O 2 . Recent advances include detection of H 2 O 2 in ischemia-reperfusion injury (20), chemiluminescent detection through a capped luciferin substrate (21), and the use of boronate-capped probes that trigger 1,6-elimination reactions on phenol generation (20).…”
Section: Sulfonylsmentioning
confidence: 99%